Academic motivation, life exploration, and psychological well-being among emerging adults in Denmark. Issue 3 (2nd July 2020) - Ozer, Simon; Schwartz, Seth J.
Abstract: Student life has been characterized both as challenging and as facilitative of future success. During the college years, emerging adults develop vocational competencies at the same time as they develop their sense of themselves and of their involvement in the world. In the current study, we examined the interplay among academic motivation, features of emerging adulthood, and psychological adaptation in relation to life satisfaction, psychological well-being, and perceived stress among Danish university students ( N  = 377). Results indicated direct and positive associations of autonomous motivation with life satisfaction, as well as a direct negative link between controlled motivation and psychological well-being. Furthermore, autonomous motivation was indirectly and positively associated with life satisfaction and psychological well-being, and negatively related to perceived stress, through experiences of life possibilities and experimentation. Controlled motivation was indirectly and positively associated with perceived stress through identity exploration. Our results underscore the importance of considering not only vocational competencies, but also personal interests and motivation, when designing educational curricula.